MOVEMENT TRANSFORMATION IN GAYO SYNTAX - Tri Murni; Robert Sibarani; Eddy Setia; Gustianigsih Gustianingsihh (Universitas Islam Sumatera Utara (UISU), 2019)
The purpose of this study is to present syntactic descriptions of how movement transformational rules apply in Gayo syntax and to examine the status of movement transformational rules in Gayo language (henceforth GL) in the theoretical framework of Transformational Linguistics (TL) proposed by Chomsky (1965, 1981) and Suhadi (2018). In this theory there are three kinds of syntactic rules: Movement Rule, Deletion Rule and Substitution Rule. The discussion focuses on Movement Transformational Rules in GL. Transformation is the inter-related process between the deep structure and the surface structure of a sentence by the application of one or more transformational rules. The method used in this study was descriptive qualitative approach as noted by Martin (2004). Descriptive research is to portray accurately the characteristics of a particular situation or group or individual with or without special initial hypotheses about the nature of these characteristics. Thus, descriptive research design was applied to give a detail description of a certain case accurately. The data were analyzed from two angles: the application and the status of movement rules in GL, which can be compulsory, optional, and restricted. The data of this research derived from some sentences in the folklore story written in GL and the invention of the writer herself as the native speaker of the language. The finding shows that all the twelve kinds of movement transformational rules proposed by Suhadi (2018) are relevant to apply in GL. After the application of movement rules, the main finding is on the status of movement transformational rules in GL in which it is found that four movement rules are compulsory, eight are optional and there is no restricted rule in the language.